Configurational changes of heme followed by cytochrome c folding reaction. Issue 1 (30th October 2014) - Choi, Jungkweon; Cho, Dae Won; Tojo, Sachiko; Fujitsuka, Mamoru; Majima, Tetsuro
Abstract : Although the reduction dynamics of ferric Cyt- c occur within a time range of a few microseconds, the ligand binding and exchange of heme, accompanied by one-electron reduction, depends on the initial configuration of the heme. Abstract : Although the folding kinetics of cytochrome c (Cyt- c ), ferric or ferrous Cyt- c, has been extensively investigated as a paradigm for a protein folding reaction using various time-resolved spectroscopic techniques, the configurational change of heme associated with the folding reaction from a ferric Cyt- c to a ferrous Cyt- c induced by one-electron reduction has not been elucidated. To address this issue, we investigated the configurational change of heme in the Cyt- c folding process induced by one-electron reduction using a combination of time-resolved resonance Raman spectroscopy and pulse radiolysis. The results presented herein reveal that the reduction of ferric Cyt- c and the ligation of Met80 occur simultaneously within a timescale of approximately 2 μs, and that the ligand binding and exchange of heme depend on the initial configuration of the heme. The rapid ligation of Met80 observed in this study may be attributed to the intramolecular diffusion of Met80 into ferrous Cyt- c with a 5-coordinated high-spin configuration. Conversely, the ligand exchange of a ferrous Cyt- c with a 6-coordinated low-spin configuration was significantly slower.